Peningkatan Pengetahuan dan Manajemen Stress Bagi Karyawan untuk Mencegah Penurunan Produktivitas Kerja - Adhi Pradiptya; Elisabeth Rotua Simamora; Teguh Ariefiantoro (Universitas 45 Surabaya, 2025)
In an increasingly competitive work environment, employees face various challenges that can trigger stress, such as work target pressure, high task demands, and an imbalance between personal life and work. Stress that is not managed properly can have a negative impact on employees' mental health, which ultimately affects productivity, job satisfaction, and the work atmosphere in the company. Therefore, companies need to take an active role in helping employees manage their stress through various strategies, one of which is stress management training. The objective of this community service is to enhance employees' understanding of the importance of identifying stress sources, developing healthy coping mechanisms, and improving mental well-being to prevent performance decline. The implementation method involves stress management training to prevent a decline in work productivity. The results of the activity showed that employees were able to understand the importance of stress management, how to manage stress at work, and set priorities using the Eisenhower Matrix and a To-Do List app, enabling them to complete tasks on time based on their priority scale.